Microalgal-based sustainable bio-fungicides: a promising solution to enhance crop yield - Rupesh Bhardwaj; Ankush Yadav; Abhishek Sahoo; Pritee Kumari; Laishram Amarjit Singh; Prashant Swapnil; Mukesh Meena; Sumit Kumar (Discover Sustainability)
Abstract The agricultural sector plays a crucial role in the world economy and in the increasing population. The decrease of crop yield and productivity by fungal infestation is one of the main concerns in agriculture. Synthetic fungicides are effective against several fungal infestations. However, although the tremendous use of synthetic fungicides to obtain high production yield has helped to cope with the growing population, it is gradually contaminating the ecosystem. Chemical fungicides have raised major concerns regarding environmental sustainability, human health, and increased resistance in fungal strains. Therefore, there is a need for a safer and more sustainable alternative. Microalgae provide a clean and sustainable solution to this emerging problem. Microalgal extracts have been reported to be a potent bio-fungicide. This review explores the efficiency, uses, and environmental advantages of using microalgal extracts as bio-fungicide. The composition of microalgal extract contains many antifungal and antimicrobial chemicals that can be used as an eco-friendly bio-fungicide. Furthermore, microalgal extracts can contribute to sustainable agriculture practices by reducing the dependence on chemical fungicides.